Growth, Yield and Uptake of P Four Variety Soybeans on Biocomposted Coastal Lands - Yani, Dewi Septi; Bertham, Yudhi Harini; Arifin , Zainal (TERRA : Journal of Land Restoration, 2024)
Soybeans (Glycine max (L.) Merrill) are a popular food commodity in Indonesia, but domestic production is still insufficient to meet the demand. To increase production, planting superior varieties on coastal land could be a viable solution. Despite the challenging biological, physical, and chemical conditions of coastal land, nutrients such as phosphorus (P) are crucial for enhancing production. Typically, the phosphorus content in the soil is lower than that of nitrogen (N) and potassium (K), and the ability of soybean plants to absorb phosphorus varies among varieties. This research aims to compare the growth, yield, and phosphorus uptake of four soybean varieties on biocomposted coastal land. The study was conducted using a Randomized Complete Block Design (RCBD) with a single factor consisting of four soybean varieties: Wilis, Anjasmoro, Malika, and Detam 1. The results indicate that the Anjasmoro, Wilis, Detam 1, and Malika varieties exhibit similar responses in phosphorus absorption. However, the Anjasmoro and Wilis varieties demonstrate better adaptability compared to Malika and Detam 1, as evidenced by their superior growth and yield. This suggests that Anjasmoro and Wilis have a higher capability to adapt to the challenging conditions of coastal land. Therefore, these two varieties are recommended for cultivation in coastal areas to boost soybean productivity, ensuring the sustainability and stability of the national food supply.